Review on Ethnomedicinal and Potential Effect of Antibacterial Plants against Halitosis - Kintoko Kintoko; Astri Desmayanti (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2022)
Halitosis is an oral malodor condition in the oral cavity that comes from the breakdown of protein by anaerobic gram-negative and gram-positive bacteria. Some bacteria that are often found in cases of halitosis are Solobacterium moorei, Porphyromonas gingivalis, Tannerella forsythia, Fusobacterium nucleatum, Prevotella intermedia, Treponema denticola, dan Streptococcus mutans. Medicinal plants to treat various diseases have shown minimal side effects. Indonesia is one of the countries that has used plants as traditional medicine since ancient times. As many as 7,000 species of medicinal plants in Indonesia have been studied to address health problems. Among the medicinal plants that have been studied are Green Betel (Piper betle L.), Cinnamon (Cinnamomum zeylanicum), Star Anise (Illicium verum), Mint (Mentha piperita) dan Oregano (Origanum vulgare) which have been shown to cure various diseases. This review article describes the potential of plants as an antibacterial against halitosis. The purpose of this review is to provide an overview of ethnomedicine and the potential effects of antibacterial medicinal plants that can be used in cases of halitosis.